2020
DOI: 10.3390/ijms21072624
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Sucrose Transporters from Vitis vinifera Confer High Yield and Enhances Drought Resistance in Arabidopsis

Abstract: Sucrose is the predominant form of sugar transported from photosynthetic (source) to non-photosynthetic (sink) organs in higher plants relying on the transporting function of sucrose transporters (SUTs or SUCs). Many SUTs have been identified and characterized in both monocots and dicots. However, the function of sucrose transporters (SUTs or SUCs) from Vitis is not clear. As the world's most planted grape species, Vitis vinifera owns three sucrose transport activity verified SUTs. In this study, we constructe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…The extract solutions were diluted with ddH 2 O to a final volume of 100 mL. Measurements were performed using an anthrone-sulfuric acid colorimetric assay, as previously described in [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…The extract solutions were diluted with ddH 2 O to a final volume of 100 mL. Measurements were performed using an anthrone-sulfuric acid colorimetric assay, as previously described in [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…VvSUC27 is a SUT located at the plasma membrane and belongs to the dicot-specific SUT1 subfamily, which includes the remaining AtSUCs ( Cai et al, 2017 ). Overexpression of VvSUCs ( VvSUC11 or VvSUC12 , or VvSUC27 ) in both tobacco and Arabidopsis conferred more rapid development, higher yield and enhanced abiotic stress resistance ( Cai et al, 2017 , 2020 ). Similarly, Cai et al (2019) reported SUTs in ‘Zuoshan-1’ ( Vitis vinifera ) responded to various stress stimuli and subsequently promoted sucrose metabolism and hormone synthesis.…”
Section: Molecular Biology Of Sink Strengthmentioning
confidence: 99%
“…The activity of sugar transporter proteins is subject to regulation [118,119]; however, very little is known about this in grapevines [11]. Expression studies in amenable species can provide useful insights into transporter function [76,120]. In order to understand function further, it is necessary to determine in which cell types a transporter is present, and few such studies have been performed in grape [2,11,121].…”
Section: Sugar Transportersmentioning
confidence: 99%